Investigation of resin infusion consumable effect on fusion bond strength in the manufacture of a thermoplastic vertical axis wind turbine prototype - Bair, Jamison, author; Bradley, Thomas H., advisor; Radford, Donald W., committee member; Heyliger, Paul R., committee member (Colorado State University. Libraries, 2020)
To further research the economic viability, manufacturability, and wider adoption of Vertical Axis Wind Turbines (VAWT), a project team led by Steelhead Composites (SHC), with assistance from Colorado State University (CSU), National Renewable Energy Laboratory (NREL), and Arkema Inc. designed and fabricated VAWT rotor assembly with thermoplastic composite blades using novel fabrication techniques. Thermoplastics present many advantages over traditional thermosets including recyclability as well as the ability to be thermally welded and reformed without machining. Thermal welding, or fusion bonding can eliminate the need for adhesive bonding, a requirement in the manufacture of thermoset and thermoplastic turbine blades, as currently being produced. Colorado State University was tasked with using Elium®, a novel liquid poly methyl-methacrylate (PMMA) thermoplastic manufactured by Arkema to conduct the manufacture of protype vertical axis wind turbine blades. Elium® is a reactive, in-situ polymerizing thermoplastic that is processed using liquid processing techniques and it has mechanical properties comparable to counterpart thermosetting resins. The CSU research team developed a resin infusion molding process with closed two-part molds to create thin, hollow fiber reinforced airfoils. When high quality airfoils were successfully manufactured the team investigated the feasibility of fusion bonding end fittings into the hollow airfoils to reduce part count and mass. It was hypothesized that the consumables that produced a rough, matrix rich texture at the bond interface would lead to higher strength bonded joints. The fusion bonding focus investigated three different infusion consumables: Compoflex® RF3 a combination release film and flow media, G-FLOW™, a structural glass fiber flow media, and Release Ply Super A, a heavy weight nylon release film. The products produced varying surface textures that were measured using a surface profilometer to compare and quantify the roughness and form of the surface, to examine how the induced surface textures impacted the quality of fusion bonded joints. This hypothesis was tested via manufacture of double lap shear strength coupons which were tested via ASTM 3528. Processing parameters of the bulk heating fusion bonding process were varied included temperature, consolidation pressure and time, and cooling method. Strength testing results in addition to failure mode analysis and digital microscopy imaging were used to determine which consumables provided a higher bond strength in both glass fiber and carbon fiber Elium® thermoplastic reinforced specimens. The results of the double lap shear tests showed that with the right combination of surface texture and processing variables, lap shear strengths of over 16 MPa (2300 psi) were achieved with glass fiber reinforcements. Results indicated that more consistent strength values were obtained from infusion consumables that had smaller surface asperities, and that larger asperities often led to the inclusion of air bubbles creating voids thus reducing the strength of the bonded joints. Subsequent testing using carbon fiber as the reinforcement provided satisfactory values for lap shear strength and the team proceeded develop a process to fusion join to end attachment plates used to attach blades to the turbine hub. After successfully fusion bonding the tower to blade attachment plates into 129" long hollow airfoil sections, post-mold reforming was used to thermoform the blades into the desired geometry to complete a three-blade vertical axis wind turbine blade prototype.
Keywords: fusion bonding; thermoplastic composite; Elium; vertical axis wind turbine; joining